2012
DOI: 10.5152/balkanmedj.2012.027
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Tramadol and Levobupivacaine Infiltration on Postoperative Analgesia in Functional Endoscopic Sinus Surgery and Septorhinoplasty

Abstract: Objective: The aim of this prospective, randomized, double-blind study was to investigate the postoperative analgesic effects of levobupivacaine or tramadol infiltration administered prior to surgery in septorhinoplasty (SRP) or endoscopic sinus surgery (ESS).Material and Methods: Sixty ASA class I-III adult patients electively undergoing SRP or ESC were included the study. Induction of anesthesia was performed with propofol 2-2.5 mg/kg, rocuronium bromide 0.6 mg/kg and fentanyl 1 μg/kg i.v. Sevoflurane 2% wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…When compared to opioids, tramadol was reported by Koputan et al to have higher VAS at 16 hours postoperative ( P = .003), PCA requirements at 20 hours ( P = .01), and total rescue analgesic consumption at 16, 20, and 24 hours (345.2 μg vs. 211.1 μg vs. 184.1 μg, P = .012, .004, and .002, respectively). However, levobupivacaine was shown to be possibly as effective as tramadol with significant differences in VAS scores between levobupivacaine and the control at 20 hours postoperatively ( P = .005) . Of the 807 included patients, 35 (4.3%) experienced nausea or vomiting.…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…When compared to opioids, tramadol was reported by Koputan et al to have higher VAS at 16 hours postoperative ( P = .003), PCA requirements at 20 hours ( P = .01), and total rescue analgesic consumption at 16, 20, and 24 hours (345.2 μg vs. 211.1 μg vs. 184.1 μg, P = .012, .004, and .002, respectively). However, levobupivacaine was shown to be possibly as effective as tramadol with significant differences in VAS scores between levobupivacaine and the control at 20 hours postoperatively ( P = .005) . Of the 807 included patients, 35 (4.3%) experienced nausea or vomiting.…”
Section: Resultsmentioning
confidence: 96%
“…Fourteen articles explored the use of local anesthetics . Of these studies, all 14 were prospective RCTs with four single‐blinded, nine double‐blinded, and one triple‐blinded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…No other systematic review or meta‐analysis was found pertaining to perioperative and postoperative analgesic use for endoscopic sinus surgeries. Thirty‐two studies met the inclusion criteria for this project: all of the included studies were randomized, controlled trials (RCTs). Using the Cochrane Bias tool, we judged 4 studies to be at high risk, 21 to be at moderate risk, 6 to be at low risk, and 1 to be at unclear risk of bias.…”
Section: Resultsmentioning
confidence: 99%